1976
DOI: 10.1139/z76-238
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of food supply by feeding territoriality in the rufous hummingbird

Abstract: This field study of female and immature migratory rufous hummingbirds (Selasphorus rufus) reveals that their feeding territories are closely regulated in size to maintain environmental reserves of energy per individual. Columbine (Aquilegia formosa) produces nectar about four times as fast per nectary as Indian paintbrush (Castilleja miniata) but territories have similar daily caloric productivity regardless of their floral species composition.Une étude en nature de femelles et d'oisilons du colibri migrateur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(56 citation statements)
references
References 20 publications
1
55
0
Order By: Relevance
“…These failings are more easily overcome with nectar-feeding birds. For example, interactions between species are commonly observed at nectar sources, which suggests interference competition, and a number of studies have shown that nectar is limiting (e.g., in a hummingbird community [Gass et al 1976]; in a honeyeater community [Ford & Paton 1976;Ford 1979]). The ease which nectar-feeding birds will use artificial sugar sources has even allowed testing of some of these ideas (S. Pimm, pers.…”
Section: Introductionmentioning
confidence: 99%
“…These failings are more easily overcome with nectar-feeding birds. For example, interactions between species are commonly observed at nectar sources, which suggests interference competition, and a number of studies have shown that nectar is limiting (e.g., in a hummingbird community [Gass et al 1976]; in a honeyeater community [Ford & Paton 1976;Ford 1979]). The ease which nectar-feeding birds will use artificial sugar sources has even allowed testing of some of these ideas (S. Pimm, pers.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals of many species of hummingbird defend a territory, the size of which is determined by food supply in terms of the number of flowers within the territory or the amount ofnectar produced by them (Gass, Angehr, & Centa, 1976;Kodric-Brown & Brown, 1978). In the course of a day, a hummingbird will visit hundreds of nectar sources and thus seriously affect the abundance and distribution of food for subsequent foraging bouts.…”
mentioning
confidence: 99%
“…These feeding territories consist of over 200 flowers (Armstrong et al, 1987;Paton & Carpenter, 1984), and the owners vigorously defend them from conspecifics attempting to rob nectar. Because flowers may take some considerable time to replenish (Gass et al, 1976), a hummingbird may follow one or several strategies in order not to revisit recently emptied flowers: visiting flowers in a consistent pattern whereby Copyright 1995 Psychonomic Society, Inc. memory is required only for the pattern and not the flowers themselves ("trap-lining";Feinsinger, 1978), visiting clumps of flowers and remembering the clump visited but not the individual flowers themselves, and remembering the specific locations of individual flowers. Each of these possible strategies has been discussed previously, and there is support from optimality models and experimental tests for the first two (Davies & Houston, 1981;Gill & Wolf, 1977;Kamil, 1978).…”
mentioning
confidence: 99%
“…Total hummingbird biomass = 2; (N~ x W~), where, for species i, W~ is its average body weight (from Gass et al 1976, Montgomerie 1979, and N~ is the number recorded on the census.…”
Section: Analysis Of Energy Demandmentioning
confidence: 99%